The Spiritual Consultancy (Jalbu/Jalabi) in the Religious Culture of Yoruba Muslims, Nigeria - Musthapa Adebayo Bello (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Spiritual consultancy (Jalbu, locally referred to as Jalabi) has been the major vocation of traditional Muslim scholars in Yoruba land, Nigeria, apart from teaching and preaching. This is accentuated by the religious culture of permissiveness which allows cross-religious interaction and sharing amongst the adherents of the three religious traditions competing for patronage in this part of the country, thereby corrupting the pristine values of Islam. Understanding this conundrum, this ethnographic work, which employs both qualitative and quantitative methods, seeks to interrogate the practice of Jalabi, its methods and approaches, and its sociological impact on Islam and the religious culture of Yoruba Muslims of Nigeria. While the majority of this research interlocutors recognize Jalabi as, among others, unacceptable before the Islamic law, damaging the image of Islam, promoting reliance on fetish rather than Allah, destroying Muslim's belief, only a few support Jalabi in a positive tone, such as making Islam relevant in solving socio-economic, political, and spiritual problems.